Media agenda in politics: how Malaysian RTM radio stations cover 14th General Election - Tham, Jen Sern; Ong, Brendan; Lim, Nichole (IIUM Press, 2020)
The media and communication technologies have changed media consumption for good, and traditional media publishers are struggling to integrate their businesses using communication technologies. However, when fake news is increasingly prevalent on social media, where everyone can be the prosumer-produce and consume news, the people seek to verify the facts through different media, and traditional media have therefore made a comeback. This research paper attempts to answer “What are the issues reported by the media”. This study provides findings made during the 14th General Election campaigning period on the political issues reported by traditional media, in this case, radio. This study used a purposive sampling method, with the sample drawn from nomination day to the voting day (April 28 – May 9, 2018); a total of 12 days. The radio stations chosen for this study are operated by a national broadcasterRadio Television Malaysia (RTM), which were Nasional FM (95.3 MHz), Ai FM (89.3 MHz) and Traxx FM (100.1 MHz). The findings showed that the news reporting patterns among the three radio stations were consistent throughout the examination period. Most of the news reported by the three radio channels were neutral but 10 RTM reports were still pro-Barisan Nasional (BN), which was the leading slant of the reports ahead of anti-PKR ones. Media-related issues (false news, imbalance news, inaccurate information) were received the second higher-ranked of issues reported by the radio channels.